Evaluation of enhanced recovery after surgery combined with percutaneous acupoint electrical stimulation in perioperative nursing of patients with gastric cancer (快速康复护理联合经皮穴位电刺激在胃癌患者围手术期的应用效果评价) - HUANG Yanying (黄艳颖); LI Wenjuan (李文娟) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of enhanced recovery after surgery combined with percutaneous acupoint electrical stimulation in perioperative nursing of patients with gastric cancer. Methods Totally 52 patients undergoing surgery for gastric cancer were randomly divided into the control group and study group, with 26 cases in each group. The control group received nursing interventions guided by the concept of enhanced recovery after surgery, and study group receive enhanced recovery after surgery combined with the percutaneous acupoint electrical stimulation. The postoperative pain was evaluated by Visual Analogue Scale (VAS). The postoperative recovery indexes and postoperative complications were measured and analyzed. Results The VAS score in the study group was lower than that in the control group (P＜0. 01). Patients in the study group had shorter time to first postoperative exhaustion, first postoperative feeding, catheter dwelling time and length of hospital stay compared with those in the control group (P＜0. 05). There was no significant difference in postoperative complication rates between two groups (P＞0. 05). Conclusion The enhanced recovery after surgery combined with the percutaneous acupoint electrical stimulation is effective to reduce the postoperative pain and improve the recovery of patients after surgery for gastric cancer, and has a positive effect on reducing postoperative complications rates. (目的 探讨快速康复护理联合经皮穴位电刺激在胃癌患者围手术期中的应用效果。方法 选取2021年3月-2022年3月医院收治的52例胃癌手术患者为研究对象, 采用随机数字表法分为对照组和试验组, 各26例。对照组接受快速康复护理, 试验组接受快速康复护理结合围手术期经皮穴位电刺激。采用视觉模拟评分(VAS)评估术后疼痛, 对比两组术后康复指标和并发症发生情况。结果 试验组术后VAS评分低于对照组, 差异有统计学意义(P＜0. 01); 试验组术后排气时间、首次进食时间、尿管留置时间、住院时间较对照组缩短, 差异有统计学意义(P＜0. 05)。两组术后并发症发生率比较, 差异无统计学意义(P＞0. 05)。结论 对行手术治疗的胃癌患者采取快速康复护理联合经皮穴位电刺激, 能够有效降低术后疼痛感, 促进患者术后康复, 对降低术后并发症发生风险具有积极意义。)